2022
DOI: 10.3389/fimmu.2022.915657
|View full text |Cite
|
Sign up to set email alerts
|

Low Protein Diets Supplemented With Alpha-Ketoglutarate Enhance the Growth Performance, Immune Response, and Intestinal Health in Common Carp (Cyprinus carpio)

Abstract: To investigate the effects of alpha-ketoglutarate (AKG) supplementation in a low protein (LP) diet on the growth performance, immune response, and intestinal health of common carp (Cyprinus carpio), 600 carp were randomly divided into five dietary groups: a normal protein (NP) diet containing 32% crude protein, an LP diet formulated with 28% crude protein, and LP with AKG at 0.4%, 0.8%, and 1.2% (dry matter). After an 8-week trial period, the results demonstrated that an LP diet led to a decrease in performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Lemire et al [ 36 ] reported that glutamate, a product of histidine catabolism, was involved in the generation of the antioxidant α-ketoglutarate, which is also considered a crucial molecule in cellular redox regulation [ 36 , 37 , 38 , 39 , 40 ]. In aquatic animals, α-ketoglutarate supplementation in the diet enhanced the antioxidant capacity in grass carp [ 41 , 42 ], hybrid sturgeon ( Acipenser schrenckii ♀× A. baerii ♂ ) [ 43 ], Songpu mirror carp [ 44 ], and common carp [ 45 ]. Hence, histidine exerts its antioxidant functions through its metabolite α-ketoglutaric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Lemire et al [ 36 ] reported that glutamate, a product of histidine catabolism, was involved in the generation of the antioxidant α-ketoglutarate, which is also considered a crucial molecule in cellular redox regulation [ 36 , 37 , 38 , 39 , 40 ]. In aquatic animals, α-ketoglutarate supplementation in the diet enhanced the antioxidant capacity in grass carp [ 41 , 42 ], hybrid sturgeon ( Acipenser schrenckii ♀× A. baerii ♂ ) [ 43 ], Songpu mirror carp [ 44 ], and common carp [ 45 ]. Hence, histidine exerts its antioxidant functions through its metabolite α-ketoglutaric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations to villus height and cytokine profile were mitigated by the addition of 1.0% AKG to the diet [ 69 ]. Carp fed low-protein diets supplemented with 0.4% AKG exhibited reduced concentrations of IL-1b and IL-6α compared to carp on low-protein diets without AKG supplementation [ 70 ]. The addition of AKG to a low protein feed improved the growth parameters and body length [ 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKG demonstrates the ability to alleviate oxidative stress in different animal models, leading to the restoration of vital antioxidant enzymes ( Table 1 ) [ 65 , 67 , 70 , 92 , 94 ]. For instance, in a mouse model of C. rodentium -induced colitis, the provision of 0.5% AKG in drinking water reduced serum concentrations of malondialdehyde and hydrogen peroxide [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations